2020
DOI: 10.3324/haematol.2019.243246
|View full text |Cite
|
Sign up to set email alerts
|

Impact and safety of chimeric antigen receptor T-cell therapy in older, vulnerable patients with relapsed/refractory large B-cell lymphoma

Abstract: Impact and safety of chimeric antigen receptor T cell therapy in older, vulnerable patients with relapsed/refractory large B-cell lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Compared with other studies of elderly R/R DLBCL treated with CAR Tcell therapy, our results were similar to those in younger R/R DLBCL patients [14][15][16][17][18][19]. Moreover, in older R/R DLBCL patients, the CR rate (51.6%) was similar to that in Lin et al's study (51%) [8] and inferior to that in the ZUMA-1 study (75%) [7]. The CGA grouping method showed that the ORR, CR, median PFS, and median OS in the fit group were higher than those in the unfit/frail group, suggesting that further stratification of DLBCL patients older than 65 years of age could help in the evaluation of treatment efficacy and more accurate prognosis prediction.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Compared with other studies of elderly R/R DLBCL treated with CAR Tcell therapy, our results were similar to those in younger R/R DLBCL patients [14][15][16][17][18][19]. Moreover, in older R/R DLBCL patients, the CR rate (51.6%) was similar to that in Lin et al's study (51%) [8] and inferior to that in the ZUMA-1 study (75%) [7]. The CGA grouping method showed that the ORR, CR, median PFS, and median OS in the fit group were higher than those in the unfit/frail group, suggesting that further stratification of DLBCL patients older than 65 years of age could help in the evaluation of treatment efficacy and more accurate prognosis prediction.…”
Section: Discussionsupporting
confidence: 88%
“…In ZUMA-1 [7] to R/R DLBCL patients who received CAR T-cell therapy, the CR rate in patients !65 years was higher than that of in patients <65 years (75% vs. 53%). Lin et al [8] reported 49 R/R DLBCL patients (24 patients >65 years, 25 patients <65 years) who received CAR T-cell therapy with a median follow-up of 179 days. The CR rate at 100 days was 51%, while the 6-month progression-free survival (PFS) and overall survival (OS) were 48% and 71%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In general, given the relatively good prognosis of typical CAR T‐cell–associated adverse events, a low threshold for ICU admission is justified. Real‐world data demonstrate that appropriately selected elderly patients older than 65 years or patients with limited comorbidities can undergo CAR T‐cell therapy and achieve favorable outcomes 81 . It has been shown that delayed ICU admission is associated with decreased chances of survival 82 .…”
Section: Clinical Management Of Patients With Serious Car T‐cell–related Toxicitiesmentioning
confidence: 99%
“…3 Recently, Lin et al reported similar safety and tolerability of older patients with lymphoma treated with commercial CD19 CAR T-cells to younger patients aged 65 years old or younger. 4 Since there were only 16 patients aged older than 65 years in our cohort (eight had ICANS), we performed the primary analysis using the age cut-off of 60 years old. Secondary analysis comparing < 65 versus ≥ 65 years-old patients showed similar findings (Tables S5-S8 and Figures S5-S7).…”
Section: Supporting Informationmentioning
confidence: 99%